2021
DOI: 10.1002/phar.2648
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of GLP‐1 receptor agonists in veterans receiving basal‐bolus insulin

Abstract: Background In 2017, an estimated 7.4 million Americans used insulin to treat diabetes. Insulin is proven to lower A1c but can result in hypoglycemia and weight gain. Combining insulin with a glucagon‐like peptide‐1 receptor agonist (GLP‐1‐RA) may provide additional blood glucose control while limiting undesirable effects including weight gain. Objective To characterize the clinical impact of adding a GLP‐1‐RA to a basal‐bolus insulin regimen in patients with type 2 diabetes. Methods This retrospective observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…11,14 There is limited evidence investigating the efficacy of premixed insulin in combination with GLP-1RAs, but studies have shown improved HbA1c, reductions in weight and insulin dose requirements, and sometimes discontinuation of bolus insulin altogether when adding GLP-1RA to basal-bolus regimens. 15,16 Biphasic insulin aspart 30/70 (BIAsp 30) is a premixed insulin product containing the analogue insulin aspart, partly in dissolved form (fast-acting; 30%) and partly in protamine crystallized form (intermediate-acting; 70%). BIAsp 30 has demonstrated improved postprandial glucose control compared with biphasic human insulin 30 (BHI 30) in a meta-analysis of T2D trials, 17 and observational studies have demonstrated that switching from BHI 30 to BIAsp 30 is associated with improved glycaemic control and reduced risk of hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,14 There is limited evidence investigating the efficacy of premixed insulin in combination with GLP-1RAs, but studies have shown improved HbA1c, reductions in weight and insulin dose requirements, and sometimes discontinuation of bolus insulin altogether when adding GLP-1RA to basal-bolus regimens. 15,16 Biphasic insulin aspart 30/70 (BIAsp 30) is a premixed insulin product containing the analogue insulin aspart, partly in dissolved form (fast-acting; 30%) and partly in protamine crystallized form (intermediate-acting; 70%). BIAsp 30 has demonstrated improved postprandial glucose control compared with biphasic human insulin 30 (BHI 30) in a meta-analysis of T2D trials, 17 and observational studies have demonstrated that switching from BHI 30 to BIAsp 30 is associated with improved glycaemic control and reduced risk of hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited evidence investigating the efficacy of premixed insulin in combination with GLP‐1RAs, but studies have shown improved HbA1c, reductions in weight and insulin dose requirements, and sometimes discontinuation of bolus insulin altogether when adding GLP‐1RA to basal–bolus regimens 15,16 …”
Section: Introductionmentioning
confidence: 99%